Impact of Farmland Abandonment on Water Resources and Soil Conservation - Lana-Renault, Noemí; Nadal Romero, Estela; Cammeraat, Erik; Llorente, José Ángel (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Farmland abandonment is one of the major land use changes occurring in many rural territories, especially in mountainous regions. Without intervention (passive land management), farmland abandonment leads to an expansion of shrubs and forest on formerly cultivated hillslopes and grazing areas. All these land use changes affect the hydrological and geomorphological dynamics of slopes and channels, having important implications for water resources and soil conservation. However, the heterogeneity of abandoned scenarios complicates the assessment of farmland abandonment on water resources and soil conservation. In this Special Issue, we will publish papers that examine the hydrological and geomorphological consequences of farmland abandonment in one (or several) of these abandoned scenarios. Our final purpose is to help water and land managers to select the most sustainable strategy (in terms of water resources and soil conservation) for the land management of marginal rural areas.